Potential Bioactivity of Guava Leaf Extract (Psidium guajava L.) as a Natural Therapeutic Agent: A Review - Risa, Risa Dwi; Septiani, Dia; Faoziyyah, Nabilla; Ananda, Meisya Dwi (Jurnal Pijar Mipa, 2025)
Guava leaves (Psidium guajava L.) from the family Myrtaceae are known to have many health benefits. This review identifies the main active compounds in guava leaves, such as flavonoids, tannins, saponins, and terpenoids, which contribute to its pharmacological activities. The purpose of this article is to evaluate the effectiveness and safety of guava leaves in providing therapeutic effects, such as antimicrobial, anti-inflammatory, and anticancer activities. A literature review with a qualitative approach of 10 articles was used in this research. Research shows that guava leaf extract is effective as an antidiabetic by inhibiting α the α-amylase enzyme and regulating glucose uptake. In addition, this extract functions as an antioxidant to fight free radicals, as well as an immunomodulator that increases phagocyte activity. The antibacterial and anti-inflammatory activities of this extract can inhibit the growth of pathogenic microbes and suppress inflammatory responses, making it potentially useful for the treatment of infection and inflammation. Anticancer activity has also been demonstrated, mainly through inhibition of cancer signalling pathways and induction of apoptosis. Thus, guava leaves have prospects as a potential natural ingredient for the development of herbal medicines to treat various health conditions, especially enzyme inhibition, increased phagocyte activity, and inhibition of inflammation and pathogenic microbial growth.